A27 Cycling for transport among children: are micro-environmental factors equally important across different street settings? An experimental study. Issue 2 (June 2015) - Ghekiere, Ariane; Van Cauwenberg, Jelle; Mertens, Lieze; Clarys, Peter; de Geus, Bas; Cardon, Greet; Nasar, Jack; Salmon, Jo; De Bourdeaudhuij, Ilse; Deforche, Benedicte
Abstract: Background: Many children worldwide fail to meet physical activity recommendations. Promoting active transport and independent mobility is a potential solution for integrating physical activity into children's daily life. Development of interventions aiming to increase these behaviours requires an understanding of key determinants. Socio-ecological models suggest that possible determinants include individual factors (e.g. attitudes), social (e.g. family) and physical (e.g. specific route characteristics) environmental factors. Most previous studies addressing this research topic were cross-sectional and limited to active transport to school, for which distance is a key barrier. However, active transport to other destinations is also of interest since children may walk or cycle locally to friends' homes or sports/leisure facilities. The purpose of the current study was to identify if micro-environmental factors determine the preference for cycling routes among children and their parents and to identify if these factors are equally important across different street settings. This study gives more insight in how to design cycling-friendly neighborhoods for children, which has scarcely been studied in the current literature. Methods: Children from 5th and 6th grade and their parents (n=305) were recruited via 12 randomly selected primary schools in Flanders, Belgium. They completed a web-based questionnaire including 12 choice-based conjoint tasks, in which they had to choose between two possible routes (depicted on manipulated photographs), to (let their child) cycle along. The routes differed in four attributes: general street setting (enclosed, half open, open), evenness of cycle path (very uneven, moderately uneven, even), speed limit (70 km/h, 50 km/h, 30 km/h) and degree of separation between a cycle path and traffic (no separation, curb, hedge). Hierarchical Bayes analyses were conducted to determine the relative importance of each micro-environmental attribute across the three street settings. Results: The evenness of the cycle path and the speed limit were the most important attributes having an effect on children's street preference, while among parents, the degree of separation and speed limit were attributes most strongly associated with the choice of street they would prefer their child to cycle along. This pattern was similar across the different street settings. Both children and their parents preferred streets with low traffic speed (vs. 50 or 70 km/h), with a separation of cycle path from traffic with a hedge (vs. a curb or no separation), and with an even cycle path (vs. moderately uneven or very uneven) across all street settings. Conclusions: The experimental use of panoramic photographs allowed to identify causal associations between micro-scale environmental factors (e.g. evenness of cycle path, speed limitations, …) and the neighborhood's appeal to cycle for transport among children. The effects of these micro-environmental factors were in the same direction across the different street settings, but differed in strength depending on the street setting. Future on-site research should confirm if changes in these micro-environmental factors actually lead to more transportation cycling among children.